Cold Agglutinin Disease With Malaria – A Case Report - R.H.DESHPANDE; R.V.KULKARNI (International Journal of Pharma and Bio Sciences, 2012)
Aim of the case report was to present a rare case of CAD with Malaria. Methods and materials were as per the clinical protocol and investigations done in the department of pathology.Cold Agglutinin Disease (CAD) is a subgroup of autoimmune Haemolytic Anemia (AIHA). Cold reactive immune globulins (agglutinins) which are directed against erythrocyte surface antigen (‘1’ antigen) are essential for the pathogenesis of CAD. Classically, the patients with CAD present with chronic anemia and acrocyanosis. Several factors like the antibody titre and the temperature range determine the ability of Cold agglutinin to induce haemolysis. The conclusion of study was that,the specific problem that occurs in the laboratory due to pathologic cold agglutinins need to be kept in mind for the accurate diagnosis. Here, we are reporting a case with of CAD in association with malaria in a 13 yrs old female.